PSYCHOLOGICAL REASONS AND ETHICAL ISSUES RELATED TO EARLY DIAGNOSIS AND INTERVENTION IN CHILDREN WITH AUTISM SPECTRUM DISORDERS - MURARU, Iulia-Diana; IORGA, Magdalena; KARNER-HUȚULEAC, Adina (Studia Universitatis Babeş-Bolyai Bioethica, 2016)
In the past few years, the reported incidence of autism has increased at a remarkably high rate across the world. However, this accelerating trend may not be due to an actual increase in the number of people who exhibit behaviors characteristic of autism, but may be attributed to other factors. This paper presents the problematic of the increased rates in Autism Spectrum Disorders and offers a brief description of early signs during the first and second years of life. The early intensive behavioral intervention is presented as being an effective method for young children with Autism Spectrum Disorders. Some psychological and ethical aspects are presented in order to point the importance and the necessity of early intervention. Rațiuni psihologice și probleme etice cu privire la diagnosticul și intervenția în cazul copiilor cu Autism. În ultima decadă, incidența cazurilor de autism a crescut, la nivel mondial, la valori foarte ridicate. Totuși, acest traiect accelerat nu poate fi cauzat doar de creșterea numărului de persoane care suferă de autism, ci poate fi atribuit și altor factori. Această lucrare prezintă problematica creșterii ratelor de autism și oferă o scurtă descriere a semnelor timpurii din primul și al doilea an de viață. Intervenția comportamentală timpurie este prezentă ca fiind o metodă eficientă de intervenție pentru copiii care prezintă această tulburare. Câteva aspecte etice și psihologice sunt menționate pentru a sublinia importanța și necesitatea intervenției timpurii. Cuvinte-cheie: tulburări din spectrul autist, diagnostic timpuriu, intervenție timpurie, etica